Acetyl-l-carnitine - Andrew Hart; Andrew Wilson; Cristina Montovani; Colette Smith; Margaret Johnson; Giorgio Terenghi; Mike Youle (2004)
Background: Nucleoside analogue reverse transcriptase inhibitors (NRTI) disrupt neuronal mitochondrial DNA synthesis, impairing energy metabolism and resulting in a distal symmetrical polyneuropathy (DSP), an antiretroviral toxic neuropathy (ATN) that causes significant morbidity in HIV disease. Serum acetyl-l-carnitine (ALCAR) levels are decreased in neuropathy associated with NRTI therapy. ALCAR enhances neurotrophic support of sensory neurons and promotes energy metabolism, potentially causing nerve regeneration and symptom relief. Objective: To assess the efficacy of oral ALCAR (1500 mg twice daily) for up to 33 months in an open cohort of 21 HIV-positive patients with established ATN. Methods: Skin biopsies were excised from the leg before ALCAR treatment, at 6–12 month intervals thereafter and from HIV-negative non-neuropathic controls. Fibre types in epidermal, dermal and sweat gland innervation were quantified immunohistochemically. Results: After 6 month's treatment, mean immunostaining area for small sensory fibres increased (epidermis 100%, P = 0.006; dermis 133%, P < 0.05) by more than that for all fibre types (epidermis 16%, P = 0.04; dermis 49%, P < 0.05; sweat glands 60%, P < 0.001) or for sympathetic fibres (sweat glands 41%, P < 0.0003). Compared with controls, epidermal, dermal and sweat gland innervation reached 92%, 80% and 69%, respectively, after 6 month's treatment. Innervation improvements continued (epidermis and dermis) or stabilized (sweat glands) after 24 month's treatment. Neuropathic grade improved in 76% of patients and remained unchanged in 19%. HIV RNA load, CD4 and CD8 cell counts did not alter significantly throughout the study. Conclusions: ALCAR treatment improves symptoms, causes peripheral nerve regeneration and is proposed as a pathogenesis-based treatment for DSP.